عہدِ سلاطینِ دہلی(1206-1526) کی معروف صوفی خواتین اور ان کی مذہبی خدماتFamous Sufi Women of Delhi Sultanate (1206-1526) and their Religious Services (Al-Qamar, 2022)
This article studies the famous Sufi Women of Delhi Sultanate and their Religious Services. It explores that with the advent of Islam in the subcontinent, many Sufis came here and spread Islam with their teachings. Their teachings were not only limited to men, but women were also able to receive their education and religious training. It was said that countless women of the subcontinent achieved perfection in the religion of Islam and played an important role in the society. He explained the purpose of Islam and taught them to live their whole life according to the Islamic teachings. Because of this education and training, the women also trained their children religiously. Bibi Zulikha, Bibi Auliya, Bibi Rasti, Bibi Khadija and Bibi Fatima are among such famous religious women. These are the women who, in good bad situation, kept themselves and their families limited to the teachings of Islam. Among them there are some women who were given spiritual strength due to their piety and devotion. This article highlights the services of these spiritual or Sufi women.
Keywords: Subcontinent; Delhi sultan; Sufi women; services